WalK(S221P), a naturally occurring mutation, confers vancomycin resistance in VISA strain XN108. (19th December 2016) - Peng, Huagang; Hu, Qiwen; Shang, Weilong; Yuan, Jizhen; Zhang, Xiaopeng; Liu, Hui; Zheng, Ying; Hu, Zhen; Yang, Yi; Tan, Li; Li, Shu; Hu, Xiaomei; et al.
Abstract : Objectives: Vancomycin-intermediate Staphylococcus aureus (VISA) strains have spread globally. We previously isolated an ST239 VISA (XN108) with a vancomycin MIC of 12 mg/L. The mechanism for XN108 resistance to vancomycin was investigated in this study. Methods: Genome comparison was performed to characterize mutations that might contribute to the XN108 resistance phenotype. The novel mutation WalK(S221P) was identified and investigated using allelic replacement experiments. Vancomycin susceptibilities, autolytic activities and morphologies of the strains were examined. Autophosphorylation activities of WalK and the WalK(S221P) mutant were determined in vitro with [λ- 32 P]ATP, and binding activity of WalK(S221P)-activated WalR to the promoter region of its target gene lytM was determined by electrophoretic mobility shift assay. Results: Genome comparison revealed three mutations, GraS(T136I), RpoB(H481N) and WalK(S221P), which might be responsible for vancomycin resistance in XN108. The introduction of WalK(S221P) to the vancomycin-susceptible strain N315 increased its vancomycin MIC from 1.5 to 8 mg/L, whereas the allelic replacement of WalK(S221P) with the native N315 WalK allele in XN108 decreased its vancomycin MIC from 12 to 4 mg/L. The VISA strains have thickened cell walls and decreased autolysis, consistent with observed changes in the expression of genes involved in cell wall metabolism and virulence regulation. WalK(S221P) exhibited reduced autophosphorylation, which may lead to reduced phosphorylation of WalR. WalK(S221P)-phosphorylated WalR also exhibited a reduced capacity to bind to the lytM promoter. Conclusions: The naturally occurring WalK(S221P) mutation plays a key role in vancomycin resistance in XN108.